1997
DOI: 10.1080/026404197367281
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of skeletal muscle ‘cramps’ during exercise: A novel hypothesis

Abstract: The aetiology of exercise-associated muscle cramps (EAMC), defined as 'painful, spasmodic, involuntary contractions of skeletal muscle during or immediately after physical exercise', has not been well investigated and is therefore not well understood. This review focuses on the physiological basis for skeletal muscle relaxation, a historical perspective and analysis of the commonly postulated causes of EAMC, and known facts about EAMC from recent clinical studies. Historically, the causes of EAMC have been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
0
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(169 citation statements)
references
References 36 publications
2
151
0
10
Order By: Relevance
“…These aforementioned findings support Schwellnus et al's (1997) 'muscle fatigue' cramping model, suggesting that 'neuromuscular fatigue' leads to abnormal neuromuscular control, namely an increase in muscle spindle afferent activity, a reduction in Golgi tendon organ afferent activity, and a resulting increase in alpha motor neuron activity and the muscle spasm observed (Schwellnus et al, 1997). The practical application of this information is that long distance triathletes need to pace themselves at speeds closer to, or slightly below, those that are practiced (O'Toole, 1989), so as to avoid excessive fatigue and resulting muscle cramps (Laursen et al, 2009).…”
Section: Muscle Crampssupporting
confidence: 81%
See 1 more Smart Citation
“…These aforementioned findings support Schwellnus et al's (1997) 'muscle fatigue' cramping model, suggesting that 'neuromuscular fatigue' leads to abnormal neuromuscular control, namely an increase in muscle spindle afferent activity, a reduction in Golgi tendon organ afferent activity, and a resulting increase in alpha motor neuron activity and the muscle spasm observed (Schwellnus et al, 1997). The practical application of this information is that long distance triathletes need to pace themselves at speeds closer to, or slightly below, those that are practiced (O'Toole, 1989), so as to avoid excessive fatigue and resulting muscle cramps (Laursen et al, 2009).…”
Section: Muscle Crampssupporting
confidence: 81%
“…Exercise-associated muscle camping is defined as involuntary painful skeletal muscle spasms that occur during or immediately after physical exercise (Schwellnus et al, 1997). In long distance triathletes, these are typically localized in the calf, hamstring or quadriceps muscles.…”
Section: Muscle Crampsmentioning
confidence: 99%
“…Neurologic fatigue and hyperexcitability 24 and imbalances in electrolytes, such as potassium, magnesium, and calcium, have also been postulated 25 to be associated with EAMCs. If given as part of the diet for long durations, acetic acid increases calcium absorption in rat intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental data are lacking, proposed theories for the cause of exerciseassociated cramping include abnormalities in substrate metabolism, fluid balance, and electrolyte concentrations, especially under extreme environmental conditions of heat or cold. 20 Consumption of a carbohydrate-electrolyte solution has been shown to delay the onset of exerciseassociated muscle cramping during calf-fatiguing exercise compared with no fluid ingestion. 21 In a study of athletes participating in an ultra-endurance run, Schwellnus et al 22 found that plasma sodium concentration at the end of the race was lower in those runners who experienced muscle cramping than in those who did not, although at nonhyponatremic values.…”
mentioning
confidence: 99%